Seeds 2 : supporting women's work around the world - Leonard, Ann, 1945-; Chen, Martha Alter; Buvinic, Mayra; Elias, Misrak; Jahan, Rounaq; Moser, Caroline (New York : Feminist, 1995)
Africa; Asia; North America; International; Afterwords.
Includes bibliographical references.
Keywords: Women in development; Women in business; Women in community development; Child care services; Women in development -- Developing counties -- Case studies; Women in business -- Developing counties -- Case studies; Women -- Employmen -- Developing countries -- Case studies